Cultivating Communication Skills through Non-Verbal Communication: A Case Study - Fatima, Ishrat; Ajmal, Muhammad; Khan, Ikramullah (Annals of Human and Social Sciences, 2024)
This study aims to explore the impact of nonverbal communication on the development of communication skills, particularly for ESL learners. Nonverbal cues, including gestures, eye gaze, facial expressions, and body language, play a crucial role in bridging communication gaps. Data collection involved the use of questionnaires and observations, with a focus on 100 male and female BS English learners at Qurtuba University D.I. Khan. The collected data underwent a comprehensive analysis using both qualitative and quantitative research principles. The anticipated outcomes of this research are expected to highlight the importance of integrating nonverbal communication strategies in ESL pedagogy. The insights gained from this study aim to assist educators in optimizing their teaching methods and contribute to the broader conversation on effective ESL instruction. Emphasizing the complementary role of nonverbal communication, this research ultimately seeks to enhance culturally responsive language learning experiences.